Fist of the North Star. Volume 10 - Buronson, 1947- (Viz signature., 2023)
"Kenshiro has at last found Yuria, the woman he loved but had given up for dead. Determined to possess her, Raoh has come to Yuria's stronghold. Kenshiro and Raoh's paths were always destined to lead them to this confrontation, the final battle to decide the successor to Hokuto Shinken. In this fight, both men will unleash the greatest secret technique passed down to them by their master, Ryuken, but only one will survive using it!"--